Cardiac arrhythmias associated with COVID-19 infection: state of the art review. (3rd October 2021) - Mohammad, Marwan; Emin, Mustafa; Bhutta, Ayat; Gul, Essa H.; Voorhees, Elijah; Afzal, Muhammad R.
ABSTRACT: Introduction: COVID-19 infection is associated with many different systemic complications. Among these, cardiovascular system complications are particularly important as these are associated with significant mortality. There are many different subgroups of cardiovascular complications, with Arrhythmias being one of them. Arrhythmias are especially important as there are a substantial percentage of patients who have arrhythmia after a COVID-19 infection, and these patients are seen with an increased mortality rate. The main interest of this review is understanding some of the specific post-COVID-19 arrhythmic complications and their predisposing factors. Areas covered: This paper will highlight the findings of studies on cardiovascular system disease after COVID-19 infection, different specific arrhythmic complications of COVID-19, and changes in electrophysiologic interventions post-COVID-19 outbreak in different centers around the world. An extensive literature search was made to find pertinent articles. Expert Opinion: Studies show us that a significant percentage of COVID-19 patients have arrhythmia. Many distinct types of arrhythmias are associated with COVID-19 infection, and specific risk factors of these arrhythmias are important as this information can be used to detect and prioritize certain at-risk patients for early treatment, which can mean life or death in some cases.